Peran Serta Wanita Dalam Program Pendampingan Pusat Kegiatan Belajar Masyarakat (PKBM) di Kota Surakarta( Tindak Lanjut Pengabdian Masyarakat STMIK Sinar Nusantara ke PKBM tahun 2004 & 2005 - Firiasih, Sri Hariyati (Jurnal Ilmiah SINUS, 2012)
The purpose of this study backdrop of In the Year 2004 and 2005 P3M Sinar Nusantara STMIK stopping PKBM never done a back field of Human Resources improvement for three PKBM by using funds in 2003 and 2004 stopping Back from the Office of Community Education. PKBM PKBM involved is Beautiful, PKBM Purwosari, PKBM Kratonan, PKBM Sinar Mentari, PKBM Dian. The results achieved quite encouraging because all activities can be implemented and useful for management PKBM Cover With the ever holding of events, it should be the sustainability of assistance programs conducted by the Sinar Nusantara STMIK and tutor to learn in the learning community at the Center for Community Learning Activities with a way to examine and know the extent of participation of women in PKBM assistance program. The research methodology was used with interview techniques, survey (observation) and questionnaires to the managers, tutors. Keywords : PKBM